Расширение сферы книгоиздания на каракалпакском языке и проблемы книготорговли - Идрисов, Р.Б (SCIENCE and SOCIETY, 2025)
The article reveals a number of problems in the sale of book products in the 1980s and 1990s, shows measures aimed at satisfying the needs of readers and increasing their interest in reading.The implementation of these works requires the formation of reading culture and universal reading culture, leads to the creation of literature aimed at strengthening national independence, forming high moral and aesthetic feelings, a sense of patriotism and devotion to the Motherland.
Keywords: disasters; Referendum; КК branch of the Academy of Sciences of the Uzbek SSR; price list; Latin script; historiography